KINERJA PENDAPATAN PETAMBAK USAHA UDANG VANAME DI LAMPUNG SELATAN - Annisa Fitri; Fadila Marga Saty; Estu Sri Luhur (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Vaname shrimp is one of Indonesia's leading export fishery commodities. The purpose of this research is to analyze the income performance of vannamei shrimp farming. Income performance was analyzed by analysis of farm income and R/C ratio. The results showed that the income of vannamei shrimp was IDR 53 269 214. Meanwhile, the performance of the vannamei shrimp business on average the R/C ratio of vannamei shrimp farming showed that it was feasible to cultivate. Based on the results of labor and capital compensation, it can be concluded that the choice to cultivate vannamei shrimp is the right one.